2019
DOI: 10.1039/c9mh00281b
|View full text |Cite
|
Sign up to set email alerts
|

Bright and fast scintillation of organolead perovskite MAPbBr3 at low temperatures

Abstract: Scintillators detect ionising radiation by converting energy deposited in them to a proportional number of photons. They are omnipresent in large-scale technical applications around us. Here, we report excellent scintillation properties of perovskites at low temperatures providing the potential for a new generation of cryogenic scintillators. One intriguing option would be replacing current medical scintillation detectors with cryogenic perovskites that could achieve higher imaging resolutions, for example for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 53 publications
3
102
0
Order By: Relevance
“…Conventional scintillators, such as thallium-doped caesium iodide (CsI:Tl) 16,17 and cerium-doped lutetium−aluminium garnet (LuAG:Ce) 18 , usually require expensive and time-consuming synthesis, which poses a major challenge for device processability. Unlike conventional scintillator materials, the emerging lead halide perovskites for X-ray detectors are starting to show attractive merits of facile fabrication, fast response and good spatial resolution [19][20][21][22][23][24][25][26] . However, the relatively low X-ray light yield, lead toxicity [27][28][29] and instability greatly limit their applications in high-end X-ray imaging featuring low-dose exposure, hazard-free manufacturing, real-time monitoring and robustness.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional scintillators, such as thallium-doped caesium iodide (CsI:Tl) 16,17 and cerium-doped lutetium−aluminium garnet (LuAG:Ce) 18 , usually require expensive and time-consuming synthesis, which poses a major challenge for device processability. Unlike conventional scintillator materials, the emerging lead halide perovskites for X-ray detectors are starting to show attractive merits of facile fabrication, fast response and good spatial resolution [19][20][21][22][23][24][25][26] . However, the relatively low X-ray light yield, lead toxicity [27][28][29] and instability greatly limit their applications in high-end X-ray imaging featuring low-dose exposure, hazard-free manufacturing, real-time monitoring and robustness.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, lead halide perovskites, such as CsPbBr 3 and MAPbBr 3 , have been demonstrated in direct X-ray imaging, owing to their strong X-ray absorption and efficient conversion to charge carriers [10][11][12][13][14][15][16][17][18][19][20] . X-ray scintillators have also been developed using highly emissive metal halide perovskite nanocrystals [21][22][23][24][25][26] . However, the toxicity of lead in these halide perovskites might limit their potential commercial applications.…”
mentioning
confidence: 99%
“…In case of perovskites, lower defect states with less charge traps, especially for single crystals endowed with smooth grain boundaries, Figure 4. In addition, between the multicomponent perovskite semiconductors, [52] MAPbBr 3 crystal exhibits a very fast and intense scintillation response, reported by Mykhaylyk et al [53] At 77 K the fast and slow components of the decay were found to be $ 0.1 ns and 1 ns, respectively. The MAPbI 3 wafer is 1 mm thick.…”
Section: X-ray and C-ray Detectorsmentioning
confidence: 66%
“…In such cases, a pertinent strategy to increase the µ-s product, bulk resistivity would be chemical doping (see Figure 4c,d). In addition, between the multicomponent perovskite semiconductors, [52] MAPbBr 3 crystal exhibits a very fast and intense scintillation response, reported by Mykhaylyk et al [53] At 77 K the fast and slow components of the decay were found to be $ 0.1 ns and 1 ns, respectively. The light yield of MAPbBr 3 was estimated as 90000 AE 18000 ph MeV À1 at 77 K and 116000 AE 23000 ph MeV À1 at 8 K. This finding underpins the potential of organic-inorganic trihalide perovskites for novel detector applications that rely on the fast timing of scintillation detectors at cryogenic temperatures.…”
Section: X-ray and C-ray Detectorsmentioning
confidence: 66%